Giant congenital melanocytic nevus scalp: report of a rare case - Bhagyalakshmi, A.; Sudhakar, P.V.; Uma, P.; Devi, P. Urmila (International Journal of Research in Medical Sciences, 2017)
Giant congenital melanocytic nevus (garment nevus) is a kind of congenital malformation of neural crest cells with size greater than 20 cm. Malignant melanoma may develop in 2-31% of these lesions. The objective of this paper is to present a unique case of giant nevus which is rare.